2020
DOI: 10.1111/jfd.13298
|View full text |Cite
|
Sign up to set email alerts
|

The role of UhpA in regulating the virulence gene expression in Edwardsiella piscicida

Abstract: Edwardsiella piscicida (E. piscicida) is an important fish pathogen. However, the mechanism of Glu6P transport regulatory protein UhpA how to affect the virulence gene expression in E. piscicida is still unclear. The results in this study showed that the metabolism‐related gene expression of cysteine synthase (orf 1134) and sulphate transporter (ychM) in the uhpA mutant strain ΔuhpA was 0.76‐fold and 0.68‐fold lower than the ones in the wild strains (p < .05). The gene expression of ethA and ethB in the ΔuhpA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A search for the term “Edwardsiella” in the NCBI database (https://pubmed.ncbi.nlm.nih.gov/) brings 1593 articles as a result (1966–2021) [access date: June/2021], with 710 (44.57%) being published between 2015 and 2021, reporting on various Edwardsiella spp. from diverse fish species and locations, as well as studies on vaccinology, immunogenicity, pathogenicity and virulence to better understand the pathogen and prevent disease (Griffin et al, 2020; Katharios et al, 2019; Leung et al, 2019; Li et al, 2020; Ye et al, 2021). These bacteria have also been linked with the infectious spleen and kidney necrosis virus in Brazil (Figueiredo et al, 2021) and are an important source of antibiotic resistance genes for other bacteria (Abdelhamed et al, 2019; Costa, Chideroli, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A search for the term “Edwardsiella” in the NCBI database (https://pubmed.ncbi.nlm.nih.gov/) brings 1593 articles as a result (1966–2021) [access date: June/2021], with 710 (44.57%) being published between 2015 and 2021, reporting on various Edwardsiella spp. from diverse fish species and locations, as well as studies on vaccinology, immunogenicity, pathogenicity and virulence to better understand the pathogen and prevent disease (Griffin et al, 2020; Katharios et al, 2019; Leung et al, 2019; Li et al, 2020; Ye et al, 2021). These bacteria have also been linked with the infectious spleen and kidney necrosis virus in Brazil (Figueiredo et al, 2021) and are an important source of antibiotic resistance genes for other bacteria (Abdelhamed et al, 2019; Costa, Chideroli, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…piscicida . For example, it was reported that Glu6P transport regulatory protein UhpA played a role in regulating the virulence gene expression (Ye et al, 2021). Metabolites in the TCA cycle promoted resistance to chloramphenicol of E .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to canonical virulence systems T3SS, T6SS, adhesion factors, haemolysin, catalase, antiserum related factor and regulator factors such as Fur and Hfq (Hu et al, 2014;Leung et al, 2019;Tan et al, 2019;Yin et al, 2018;Yoon et al, 2020;Zhang et al, 2018Zhang et al, , 2019, some novel virulence genes and resistance genes were also identified in E. piscicida. For example, it was reported that Glu6P transport regulatory protein UhpA played a role in regulating the virulence gene expression (Ye et al, 2021). Metabolites in the TCA cycle promoted resistance to chloramphenicol of E. tarda (Wang, Dong, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%